Morfem Terikat Pada Buku Cerita Rakyat Nusantara 34 Provinsi - Reni Rokhayati; Ila Nafilah; Yulia Aguatin (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2023)
This research aims to find and describe bound morphemes contained Indonesian Folklore from 34 Provinces. This research uses Morphological theory. This research uses a qualitative descriptive method with Content Analysis techniques. The results of this research are: (1) There are 233 prefixes in Folklore of the Archipelago from 34 Provinces consisting of 6 prefixes (2.6%), 10 prefixes (4.3%), prefixes in- as many as 20 findings (8.6%), Prefix Men- as many as 44 findings (18.9%), Prefix me- as many as 48 findings (20.6%), Prefix me0n- as many as 60 findings (25.7%), prefix mem- as many as 40 findings (17.1%), prefix se- many as 5 findings (2.1%). There are 200 suffixes in Indonesian Folklore, the suffix -an totaling 50 findings (25%), the suffix -kan 100 findings (50%), and the suffix  -nya 50 findings (25%).